Design, synthesis and biological evaluation of 9-aryl-5H-pyrido[4,3-b]indole derivatives as potential tubulin polymerization inhibitors - Shi, Lingyu; Yang, Shanbo; Chang, Jing; Zhang, Yujing; Liu, Wenjing; Zeng, Jun; Meng, Jingsen; Zhang, Renshuai; Wang, Chao; Xing, Dongming (Frontiers in Chemistry, 2022)
A series of new 9-aryl-5H-pyrido[4,3-b]indole derivatives as tubulin polymerization inhibitors were designed, synthesized, and evaluated for antitumor activity. All newly prepared compounds were tested for their anti-proliferative activity in vitro against three different cancer cells (SGC-7901, HeLa, and MCF-7). Among the designed compounds, compound 7k displayed the strongest anti-proliferative activity against HeLa cells with IC50 values of 8.7 ± 1.3 μM. In addition, 7k could inhibit the polymerization of tubulin and disrupt the microtubule network of cells. Further mechanism studies revealed that 7k arrested cell cycle at the G2/M phase and induced apoptosis in a dose-dependent manner. Molecular docking analysis confirmed that 7k may bind to colchicine binding sites on microtubules. Our study aims to provide a new strategy for the development of antitumor drugs targeting tubulin.